Treating COVID-19 using Micro RNA - Eskandar Kirolos (Journal de la Faculté de Médecine d'Oran)
Over 7,805,583 people worldwide are susceptible to death because of infection by an encountered microscopic virus known as Coronavirus. Actually, it is a family of infectious viruses that was first discovered for about 50 years by a group of virologists.